Acute otitis media: antibiotics are moderately effective and mildly increase the risk of adverse effects; prevalence of different causative bacteria changed after introduction of the heptavalent pneumococcal conjugate vaccine. Issue 6 (11th May 2011) - Sox, Colin
Abstract : Commentary on: Coker TR Chan LS Newberry SJ . Diagnosis, microbial epidemiology, and antibiotic treatment of acute otitis media in children: a systematic review . JAMA 2010 ;304 :2161 –9 .